Production Operational Monitoring Application (Case Study: CV.Chavasindo Jaya) - Diana, Nur; Kurniawan, Helmi (Marcha Institute, 2023)
CV. Chavasindo Jaya is engaged in production which is located at Jl. Paya Geli, Sunggal, Deli Serdang Regency, North Sumatra 20351. The products produced are soap and hair vitamins. The problem that occurs is that the head of production cannot always monitor production operations because there are many operations handled and the head of production tends to only see based on reports received from the production administration on weekends, so production operational errors often occur, for example production results are not balanced with operational needs and this can be detrimental to the company because the leadership does not directly know the operations that occur every day. This study aims to make it easier for the head of production to monitor production operations so that errors in production operations no longer occur. This study uses Web and Android applications for monitoring the production operations of CV. Chavasindo Jaya. With the production operational monitoring application, it can make it easier for the head of production to monitor production operations.